Genealogi dan Pengaruh Ideologi Jihadisme Negara Islam Iraq dan Suriah (NIIS) di Indonesia - Masdar Hilmy (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2014)
This paper tries to analyze the ideology of jihadism as developed by the Islamic State of Iraq and Syria (ISIS), its genealogy and its influence in Indonesia. This paper argues that ISIS does not represent the replica of other jihadist ideologies and movements such as al-Qaeda, regardless of its historical relation in the past. Rather, ISIS represents itself, a focal point where its ideologues eclectically coin and pick some religious doctrines with their own way and method. Even though ISIS claims that it follows Sunnî school of thought, in reality it poses extreme ideology which diametric-ally differs from the mainstream Sunnî ideology. Due to its extreme ideology, its existence has been rejected not only by the mainstream Muslim scholars, but also by their fellow jihadists. Despite such a rejection, it still appeals tacit sympathy and support from some jihadist group in Indonesia such as Ba’asyir’s led-Jama’ah Anshorut Tauhid (JAT) and Santoso’s clandestine Mujahidin Indonesia Timur. Keywords: NIIS, jihadisme, khilâfah, al-Qaeda, JAT.